Physical Aspects of Viral Membrane Fusion - Laura Wessels; Keith Weninger (The Scientific World Journal)
Enveloped viruses commonly employ membrane fusion during cell penetration in order to deliver their genetic material across the cell boundary. Large conformational changes in the proteins embedded in the viral membrane play a fundamental role in the membrane fusion process. Despite the tremendously wide variety of viruses that contain membranes, it appears that they all contain membrane fusion protein machinery with a remarkably conserved mechanism of action. Much of our current biochemical understanding of viral membrane fusion has been derived from high-resolution structural studies and solution-based in vitro assays in which viruses fuse with liposomes or cells. Recently, single-particle experiments have been used to provide measurements of details not available in the bulk assays. Here we focus our discussion on the key dynamical aspects of fusion protein structure, along with some of the experimental and computational techniques presently being used to investigate viral-mediated membrane fusion.